The molecular relaxation mechanisms in cork as studied by thermally stimulated discharge currents - Mano, J F; Correia, N T; Moura Ramos, J J; Saramago, B (Journal of Materials Science, 1995)
The dielectric relaxation mechanisms present in cork have been investigated in the temperature range -100 to 100~ using the technique of thermally stimulated discharge currents. A relaxation mechanism was detected which showed a compensation behaviour as observed for the a-relaxation (or glass transition relaxation) of synthetic polymers and which lead us to attribute to cork a glass transition-like temperature of 18~ One lower temperature mechanism was also observed, with low activation enthalpy and entropy, which is presumably originated by local motions (internal rotations) of polar molecular groups. An upper Tg relaxation of higher intensity was also detected which was attributed to large-scale non-cooperative motions of polymeric segments.
Keywords: Cork; dielectric relaxation (Voyant); thermally stimulated discharge currents (TSDC)